Neither here nor there: the experiences of Zimbabwean migrant children and youth - Chirongoma, Sophia (University of KwaZulu-Natal, 2022)
This article is an auto-ethnographic exploration of how migration presents numerous adjustment challenges for Zimbabwean migrant children and youth. The author presents an auto-ethnographic account of how her son Tadiwanashe had to contend with numerous life-changing experiences throughout the migration path. The article illuminates the various ways in which children and youth who have migrated from Zimbabwe with their parents in search of greener pastures often find themselves struggling with an identity crisis. Hence, they find themselves neither belonging in the diaspora nor in their motherland. This puts them in a quagmire whereby they feel as if they are ‘neither here nor there’. The article also foregrounds the various coping and survival strategies adopted by the migrant children and youth as they navigate their new spaces. It takes note of how they exercise their agency, resilience and creativity as they grapple with the changes thrust upon them due to parental migration. In concluding, the article reiterates the need for academic researchers to pay particular attention to the fact that children and youth should not be perceived as passive participants during the migration process, rather, their voices also deserve to be heard.